ПЕРИОДИЗАЦИЈАТА НА МАКЕДОНСКИОТ ЛИТЕРАТУРНО-КУЛТУРЕН РАЗВИТОК (Philological Studies, 2019)
As a small people, without state (at least without own-national state tradition), non-free and divided in the 10th century, similarly to the Slovenians, Slovaks, Byelorussian and Ukrainians in the Slavic world, the Macedonians had a non-regular and late literary development. Despite of the 1000-years literacy tradition and situated in a region that should suppose a European literacy process, Macedonia was the last in gaining the freedom and the foundation of national state on the only a part of its ethnical territory. Accordingly, in the specific historical circumstances Macedonia was the last who has promoted its polyvalent literature and culture. The non-typical continuity of the literarycultural processes during the whole Macedonian history up to the foundation of the national state (1944), dictate the methodological approach to the periodisation of the Literary-cultural development.